If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 = 2(x + -1) + -4 Reorder the terms: 16 = 2(-1 + x) + -4 16 = (-1 * 2 + x * 2) + -4 16 = (-2 + 2x) + -4 Reorder the terms: 16 = -2 + -4 + 2x Combine like terms: -2 + -4 = -6 16 = -6 + 2x Solving 16 = -6 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 16 + -2x = -6 + 2x + -2x Combine like terms: 2x + -2x = 0 16 + -2x = -6 + 0 16 + -2x = -6 Add '-16' to each side of the equation. 16 + -16 + -2x = -6 + -16 Combine like terms: 16 + -16 = 0 0 + -2x = -6 + -16 -2x = -6 + -16 Combine like terms: -6 + -16 = -22 -2x = -22 Divide each side by '-2'. x = 11 Simplifying x = 11
| 4(3x+5)=104 | | 7.50=0.8c+0.5c | | 11=-7p+13+8p | | 6x-50=10-x | | 2m+23=7m-2 | | 0.5c-7.50= | | x^2-3x+24=0 | | 17x^2-22x+6=0 | | -4x+-40-6=-3-6 | | 4+4b=4 | | 7n-18+1=19 | | 8.2(s+4)=6.7x+5.2 | | b-2+3b+6=4 | | 6p-1=p+20 | | 6(x+8)=7X+3 | | 27*x=1800 | | 6(X+8)=7x-3 | | -6+3X-3Y=0 | | 0=-Y+X-4 | | -3+2X=Y | | 7x+5x+10= | | y+5=-10(X-1) | | 18x^2-47x-56=0 | | 3+(5a+5)=35 | | -1-9x=9x+19 | | 15*x^10=67 | | 7(4b-1)=-3b-2 | | 3(2m-10)=2m+10 | | 20=14m-9+3(5m) | | 17-x=3x-7 | | 8x-6=-2(6x+4)+2x | | x^5-4x^4+x^3+2=0 |